PELATIHAN MATEMATIKA BAGI SISWA-SISWI KELAS 6 SEKOLAH DASAR DALAM PROGRAM SIAP UJIAN NASIONAL - Attin Warmi; Rafiq Zulkarnaen; Alpha Galih Adirakasiwi (JUARA: Jurnal Wahana Abdimas Sejahtera, 2020)
This program is one of the community service programs carried out by groups of lecturers and student representatives of the mathematics education program at UNSIKA. This program is in the form of providing tutoring outside school hours to elementary school students in mathematics. Most students are of the view that mathematics is difficult, the scores obtained in the National Examination are still lacking. Based on these conditions, we will design a program to assist schools in providing tutoring for their students in facing the National Examination. The form of the program is in the form of providingtutoring for elementary school students, to facilitate student learning in facing the National Exam in the National Examination Ready program. For the implementation of this activity, the mathematics textbooks and modules that are designed for guidance and study must be prepared. The material to be applied is about mathematics material that has been summarized from first grade to sixth grade material. The structure of teaching materials for each topic begins with concepts, example questions, exercises, discussion and key answers. The textbook is ready to be used for the program.